Study on The Addition of Red Ginger (Zingiber officinale Var. Rubrum) and Black Rice (Oryza sativa L. Indica) to The Organoleptic Evaluation and Physical-Chemical Properties of Robusta Coffee (Coffea canephora) from Southeast Sulawesi - Nur Asyik; Dhian Herdiansyah; Muhammad Syukri Sadimantara (Postgraduate, University of Mataram, 2025)
This study aims to determine the effect of adding red ginger and black rice on the organoleptic and physicochemical properties of robusta coffee. The problem in this study arose because, so far, the caffeine content in coffee has generally been high. On the other hand, the addition of red ginger and black rice can reduce caffeine levels and improve the taste of coffee. This study employed a factorial Completely Randomised Block Design with two factors. The first factor is the addition of red ginger (J) at three levels: 4% (J1), 8% (J2), and 12% (J3). The second factor is the addition of black rice (B) at two levels: 10% (B1) and 20% (B2). Organoleptic data were analyzed using ANOVA and DMRT tests. Physicochemical properties were analyzed descriptively. The results of the study showed that the best treatment was with the addition of 12% red ginger and 20% black rice (J3B2), with a color of 3.75 (like), aroma 3.90 (like), texture 4.00 (like), and taste 4.03 (like), water content 1.113%, ash 3.657%, pH 5.83, caffeine 0.72%, chlorogenic acid 4.92%, and antioxidant activity (IC50) 39.28 ppm